Evaluation of soft tissue tumors with immunohistochemistry correlation - Puja Bhavesh Jarwani; Sneha Samir Babaria; Deepak Shyamsunder Joshi; Sushil Kundanlal Suri (Al Ameen Medical College, 2022)
Background: Soft tissue tumors (STTs) are heterogeneous group of tumor and Immunohistochemistry (IHC) has assumed an increasingly important role in their diagnosis. Objectives: To estimate the relative frequency of various STTs with age, gender and site wise distribution, study their histomorphological spectrum, grade the soft tissue sarcomas and evaluate the role of IHC. Materials and Methods: This observational study was conducted in tertiary care hospital and cases diagnosed as STTs from January 2018 to December 2020 were included in the study. Clinical findings were obtained from patients' case files. Histological findings were evaluated and grading was done in soft tissue sarcomas. IHC was performed wherever required. Descriptive and comparative statistical analysis was performed. Results: STTs were encountered more in female than male. Benign STTs were more common than malignant. Incidence of malignancy increased with age, malignant tumors being most common in fifth decade. Adipocytic tumors (n=162, 63.8 %) formed major bulk of benign tumors. Most common malignant STTs were smooth muscle tumors (n=6, 23.1 %). IHC was very important in diagnosis of STTs because of frequent difficulty of diagnosis on morphological basis alone. Conclusions: Adipocytic tumors were most common benign STTs and most common malignant STTs were smooth muscle tumors.